Enantiopure substituted pyridines as promising antimalarial drug candidates. Issue 15 (10th April 2020) - Bentzinger, Guillaume; Pair, Etienne; Guillon, Jean; Marchivie, Mathieu; Mullié, Catherine; Agnamey, Patrice; Dassonville-Klimpt, Alexandra; Sonnet, Pascal
Abstract: We describe the enantioselective synthesis and biological evaluation of 4-(2-amino-1-hydroxyethyl)pyridines (4 AHPs) as new antimalarial drug candidates. In particular, two routes to obtain the key-intermediate 4-vinyl-pyridine were studied. These routes are based on a Kröhnke-type cyclization or on metal-catalyzed reactions. The Kröhnke-type cyclization route is faster but only efficient at low scale since this pathway involves a Wittig reaction that requires severe temperature-control. Consequently, we designed a second route based on metal-catalyzed reactions. This way is longer but the 4-vinyl-pyridine can be obtained on a 5 g scale at least. Finally, a regioselective SN 2 ring-opening of enantiopure epoxides by alkyl primary amines allowed the synthesis of eight 4-AHPs with global yields up to 41%. These compounds show strong in vitro antimalarial activity against P. falciparum strains and are more active that chloroquine and mefloquine. These results demonstrate that 4-AHPs are promising antimalarial drug candidates. Graphical abstract: Image 1 Highlights: Enantiopure substituted pyridines as new promising antimalarial drug candidates. Key-intermediate obtained according two routes based on a Kröhnke-type cyclization or on metal-catalyzed reactions. 4-substituted pyridines show strong in vitro antimalarial activity against P. falciparum 3D7 and W2 strains.